WHEN RITUAL MEETS ACCOUNTING: EXPLORING THE MEANING OF COST ACCOUNTABILITY IN MANGGARAI'S KENDURI CEREMONY - Nuraini Ismail; Lilik Purwanti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to determine the cost sharing system incurred in the traditional kenduri ceremony (Di'a class) and to reveal the meaning of cost accountability in Wae Renca Village, West Cibal District, Manggarai Regency, East Nusa Tenggara Province. This study uses a qualitative method with a descriptive approach. Data were obtained through observation, interviews with traditional elders, nuclear families, children of rona, and children of wina, as well as documentation and literature studies. The results of the study indicate that the cost sharing system in the Kenduri ceremony is regulated based on customary agreements and involves three main parties, namely ase kae (nuclear family), children of rona (siblings), and children of wina (sisters). Cost accountability is reflected in the family deliberation mechanism, where every contribution and expenditure is recorded and accounted for openly. The meaning of cost accountability in the kenduri ceremony reflects five main values, namely: (1) Religious meaning as a form of accountability to God and ancestors; (2) Humanitarian meaning as respect for human dignity; (3) The meaning of unity and togetherness through collective participation of the entire family; (4) The meaning of deliberation which emphasizes the importance of joint decisions; and (5) The meaning of justice in the distribution of costs without differentiating economic status. This study concludes that cost accountability in the kenduri ceremony not only functions economically, but also become a symbol of the spiritual, social, and cultural values of the Manggarai people which strengthen solidarity and collective responsibility.